The Impact of Democratization and International Exposure to Indonesian Counter-Terrorism - Wibisono, Ali Abdullah (Global: Jurnal Politik Internasional, 2017)
This article explains the influence of the United States of America to Indonesian counter-terrorism. Two aspects of counter-terrorism are explained: effectiveness and adherence to human rights values. It argues that America’s emphasis on the need to forge security cooperation in responding to terrorism facilitated human rights values to be adopted as justification of counter-terrorism, rather than a balancer to its effectiveness. Indonesia’s cooperation with the U.S in counter-terrorism has facilitated the growth of the restitutive or kinetic measures, but neglects a strengthening of political leadership over institutional development of counter-terrorism. The latter can be judged from the absence of policy-evaluation, strategy document, and joint capacity-development of other agencies responsible for counter-terrorism. In the long run, this paper argues, the lack of political leadership nurtures the tradition impunity to the security apparatuses in the conduct of counter-terrorism.